Alkali-activated binders with reclaimed asphalt aggregates as a potential base layer of pavements - Costa, Juliana Oliveira (2022)
The pavement infrastructure comprises 16.3 million kilometres worldwide, and the pavement-related industrial sectors are said to be responsible for 21% of the global Greenhouse Gas (GHG) emissions worldwide (Plati, 2019). Sustainable actions on materials for those pavement layers mostly consider replacing (i) natural aggregates (NA) with recycled ones and (ii) Portland cement (PC) used as binder/stabiliser with binders with a lower ecological footprint. This research investigates the possibility of incorporating recycled asphalt pavement (RAP) as an aggregate replacement and alkali-activated material (AAM) as Portland cement (PC) replacement in/for base layer materials. So far, most studies focused on the use of RAP and PC or supplementary cementitious materials. The combination of RAP with alkali-activated matrices may be an even more sustainable solution, given that not only the aggregate is recycled, but also PC is absent from the matrix. Properly designed AAMs are stronger and more durable than PC-based materials. It is, therefore, very likely that the employment of RAP in AAM will result in materials that achieve the minimum requirements for road applications. This research produced an alkali-activated material containing fine and/or coarse RAP aggregates (RAP-AAM) as a replacement for natural aggregates to be used as base layers of pavements. The main objective of this thesis is to determine whether AAM can incorporate high amounts of RAP and be used as pavement base layers without compromising mechanical and durability performance. During this research, two innovative characterization methods were used as an alternative to those often employed for Portland concrete. Firstly, the observation of the interfacial transition zone (ITZ) was improved by combining a laser scanning confocal microscope (LSCM) and a scanning electron microscope (SEM). The combination of both techniques permitted a better observation of the heterogeneous asphalt coating of the RAP particles, the presence of clusters, and cracks at the border and within the activated matrix. Secondly, the thesis proposes an alternative methodology to observe and quantify the shrinkage of RAP-AAM or any other cementitious materials by employing simplified optical imaging. Although this method only allows for the observation of total shrinkage, it is an almost inexpensive method that could give a clear indication of volume changes over time. The experimental data demonstrated that an ideal alkali-activated binder composition to produce RAP-AAM lean concrete would have 10% MK replacement (BFS vol%) and the activator would have 8% Na2O and Ms= 0 (i.e., activated with NaOH and no sodium silicate). This selection was based on the minimum activator amount required to reach the target compressive strength for a weak to medium lean concrete (5 to 10 MPa), while also minimizing the shrinkage effect. The durability assessment to freeze and thaw indicated similar performance for RAP-AAM and reference (RAP-PC). The findings of this research showed that RAP-AAM is a promising material for pavement base layers and more investigation is needed on long-term strength and durability.